HUBUNGAN PENGARUH INTERPERSONAL DAN SITUASIONAL DENGAN UPAYA PREVENTIF PADA PEREMPUAN PENDERITA KANKER PAYUDARA (Correlation Between Interpersonal and Situational Influence with Preventive Efforts in Breast Cancer Survivor) - Nastiti, Aria Aulia; Armini, Ni Ketut Alit; Ulazzuharo, Chiza (Fakultas Keperawatan, Universitas Katolik Widya Mandala Surabaya, 2017)
Introduction,Breast cancer is type of cancer with highest amount of sufferer cancer in Surabaya, including in Puskesmas Kenjeran. From interview result with women of childbearing age in puskesmas Kenjeran, From interviews with women of childbearing age in the clinic Kenjeran , there are still many women who do not take steps to prevent. Women’s prevention against breast cancer is still low, it can effect in about 80% of total cancer sufferer treatment when has reached in advanced stage, so that it can reduce the success of treatment. The study aims to determine the effect of interpersonal relationships and situational and the prevention of breast cancer in women of childbearing age. Method, This study used a descriptive correlational research design with cross sectional approach. Population in this research is 5.340 women of childbearing age at Kelurahan Bulak and Kelurahan Kenjeran Surabaya. The sampling technique used the cluster sampling and obtained 100 samples. Independent variable in this research are interpersonal influence and situasional influence. Dependent variable in this research is primary and secondary prevention of breast cancer. Data analysis using Spearman rho’s statistical tests to determine which variables are associated with the prevention of breast cancer. Result,This research show that there is no correlation between interpersonal influence and prevention of breast cancer with p value= 0,150 (α ≤ 0,05). At the same time for correlation between situational influence variable and prevention of breast cancer variable result p value = 0,043 (α ≤ 0,05).Conclusion and Discussion, It showed that there is no correlation between interpersonal influence with prevention of breast cancer and there is a correlation between situational influence with prevention of breast cancer in women of childbearing age. Interpersonal influence can’t increase the breast cancer prevention in women of childbearing age at Puskesmas Kenjeran , whereas situational influences may increase breast cancer preventive efforts in Puskesmas Kenjeran Surabaya.